1990
DOI: 10.1016/s0022-5347(17)39909-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and Enzyme Histochemical Localization of Peptidergic, Aminergic and Cholinergic Nerve Fibers in the Rat Seminal Vesicle

Abstract: The distribution of the autonomic nervous system in the rat seminal vesicle was studied with immuno- and enzyme-histochemistry. In the smooth muscle layer, a large number of neuropeptide Y (NPY)- and tyrosine hydroxylase (TH)-immunoreactive nerve fibers were observed, while few fibers were distributed in the mucosal layer. A small number of substance P-immunoreactive fibers were present only in the smooth muscular layer, but vasoactive intestinal polypeptide (VIP)-immunoreactive fibers were abundantly distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…This finding accords with the results of previous studies describing the distribution of nerve fibres containing acetylcholinesterase (AChE) or VAChT in the human SV (Gosling and Dixon, 1994;Sjöstrand et al, 1998;Dixon et al, 2000) as well as in the SV and BU of guinea pigs (Al-Zuchair et al, 1975;Sjöstrand et al, 1998), rats (Moss et al, 1987;Yuri, 1990) and hamsters (Pinho et al, 1994;Chow et al, 1997).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding accords with the results of previous studies describing the distribution of nerve fibres containing acetylcholinesterase (AChE) or VAChT in the human SV (Gosling and Dixon, 1994;Sjöstrand et al, 1998;Dixon et al, 2000) as well as in the SV and BU of guinea pigs (Al-Zuchair et al, 1975;Sjöstrand et al, 1998), rats (Moss et al, 1987;Yuri, 1990) and hamsters (Pinho et al, 1994;Chow et al, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…A more or less equal density of noradrenergic nerve fibres was found in the mucosa and muscular layer of the BU and SV, which is consistent with the results previously obtained in humans (Gu et al, 1983;Chapple et al, 1991;Hedlund et al, 1997) and pigs (Kaleczyc et al, 1999). It must be mentioned that in other studies of the SV of humans (Gosling and Dixon, 1994; as well as rats (Owman and Sjöstrand, 1965;Moss et al, 1987;Yuri, 1990) and guinea pigs (Owman and Sjöstrand, 1965;Wakade and Kirpekar, 1971;Al-Zuchair et al, 1975) noradrenergic nerve fibres were found only in the muscular layer. Astonishingly, in the disseminated part of the ovine prostate only single nerve fibres displayed the presence of TH and DβH, which significantly differs from the previously described abundant innervation of this gland in man (Vaalasti and Hervonen, 1980), rat (Vaalasti and Hervonen, 1979) or pig (Kaleczyc et al, 1999), but is similar to that reported for the guinea pig, dog, cat, rabbit (Owman and Sjöstrand, 1965;Sjöstrand, 1965) and hamster (Chow et al, 1997).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Besides noradrenaline Immunohistochemical properties of nerve fibres supplying accessory male genital glands in the pig. A colocalisation study (and presumably acetylcholine), a variety of other substances have been identified in these nerves, such as neuropeptide Y (NPY), vasoactive intestinal polypeptide (VIP), calcitonin gene-related peptide (CGRP), substance P (SP), enkephalins (ENK), somatostatin (SOM), serotonin, peptide histidine isoleucine, gastrin-releasing peptide, bombesin, pituitary adenylate cyclase-activating peptide, helospectin and nitric oxide synthase (Alm et al 1978(Alm et al , 1980(Alm et al , 1981Vaalasti et al 1980Vaalasti et al , 1986Gu et al 1983;Stjernquist et al 1983;Adrian et al 1984;Lamano Carvalho et al 1986;Higgins and Gosling 1989;Lange and Unger 1990;Yokoyama et al 1990;Yuri 1990;Crowe et al 1991;Properzi et al 1992;Iravani and Zar 1994;Jen et al 1995Jen et al , 1996Tainio 1995;Afonso et al 1996;Hedlund et al 1996;Chow et al 1997).…”
Section: Introductionmentioning
confidence: 99%